Analisis Pandangan SDN 13Surau Gadang Terhadap PengembanganOrganisasi di KotaPadang - Nur faizah (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
This study aims to analyze the views of SDN 13 Surau Gadang regarding educational organizational development in Padang City. The main objective of this study is to understand how school administrators improve learning and apply organizational development concepts to increase student self-confidence and work efficiency. The research method used is descriptive qualitative, involving observation and in-depth interviews. The research findings indicate that SDN 13 Surau Gadang has a positive view of organizational development, which is manifested in collaborative efforts in planning, implementing, and evaluating school programs. However, several issues remain, such as daily limitations and a lack of ongoing training for educators. Overall, organizational development at SDN 13 Surau Gadang shows a progressive trend, although it still requires improvements in management and active participation from all school personnel.